A rare case of extremely high counts of circulating tumor cells detected in a patient with an oral squamous cell carcinoma. Issue 1 (December 2016) - Wu, Xianglei; Mastronicola, Romina; Tu, Qian; Faure, Gilbert; De Carvalho Bittencourt, Marcelo; Dolivet, Gilles
Abstract Background Despite aggressive regimens, the clinical outcome of head and neck squamous cell carcinoma remains poor. The detection of circulating tumor cells could potentially improve the management of patients with disseminated cancer, including diagnosis, treatment strategies, and surveillance. Currently, CellSearch® is the most widely used and the only Food and Drug Administration-cleared system for circulating tumor cells detection in patients with metastatic breast, colorectal, or prostate cancer. In most cases of head and neck squamous cell carcinoma, only low counts of circulating tumor cells have been reported. Case presentation A 56-year-old white male with no particular medical history, was diagnosed with a squamous cell carcinoma of oral cavity. According to the imaging results (computed tomography and18 F-fluorodeoxyglucose positron emission tomography / computed tomography) and panendoscopy, the TNM staging was classified as T4N2M0. A non-interruptive pelvimandibulectomy was conducted according to the multidisciplinary meeting advices and the postoperative observations were normal. The patient complained of a painful cervical edema and a trismus 6 weeks after the surgery. A relapse was found by computed tomography and the patient died two weeks later. The search for circulating tumor cells in peripheral venous blood by using the CellSearch® system revealed a very high count compared with published reports at three time points (pre-operative: 400; intra-operative: 150 and post-operative day 7: 1400 circulating tumor cells). Of note, all detected circulating tumor cells were epidermal growth factor receptor negative. Conclusion We report here for the first time a rare case of oral squamous cell carcinoma with extremely high circulating tumor cells counts using the CellSearch® system. The absolute number of circulating tumor cells might predict a particular phase of cancer development as well as a poor survival, potentially contributing to a personalized healthcare.